PENGARUH CORPORATE GOVERNANCE DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Ellysia Bernadeth; Muhammad Arief Effendi (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence about the effect of managerial ownership, institutional ownership, leverage, firm size, profitability, audit committee, board size, and fixed asset turnover to earnings management. Sample used in this research are all manufacturing companies listed in Indonesia Stock Exchange consistently during the period from 2018 until 2020. Sample selection method used was purposive sampling, there were 73 companies met the criteria, resulting 219 data are taken as sample. The analysis was performed using multiple linear regressions analysis method. The results of this research show that proportion of firm size and fixed asset turnover affect earnings management, while managerial ownership, institutional ownership, leverage, profitability, audit committee, and board size have no effect to earnings management.